PDE3 Inhibition Reduces Epithelial Mast Cell Numbers in Allergic Airway Inflammation and Attenuates Degranulation of Basophils and Mast Cells - Beute, Jan; Ganesh, Keerthana; Nastiti, Hedwika; Hoogenboom, Robin; Bos, Vivica; Folkerts, Jelle; Schreurs, Marco W. J.; Hockman, Steve; Hendriks, Rudi W.; KleinJan, Alex (Frontiers in Pharmacology, 2020)
Epithelial mast cells are generally present in the airways of patients with allergic asthma that are inadequately controlled. Airway MCs are critically involved in allergic airway inflammation and contribute directly to the main symptoms of allergic patients. Phosphodiesterase 3 (PDE3) tailors signaling of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), which are critical intracellular second messenger molecules in various signaling pathways. This paper investigates the pathophysiological role and disease-modifying effects of PDE3 in mouse bone marrow-derived MCs (bmMCs), human LAD2- and HMC1 mast cell lines, human blood basophils, and peripheral blood-derived primary human MCs (HuMCs). In a chronic house dust mite (HDM)-driven allergic airway inflammation mouse model, we observed that PDE3 deficiency or PDE3 inhibition (PDE3i) therapy reduced the numbers of epithelial MCs, when compared to control mice. Mouse bmMCs and the human HMC1 and LAD2 cell lines predominantly expressed PDE3B and PDE4A. BmMCs from Pde3-/- mice showed reduced loss of the degranulation marker CD107b compared with wild-type BmMCs, when stimulated in an IgE-dependent manner. Following both IgE-mediated and Substance P-mediated activation, PDE3i-pretreated basophils, LAD2 cells and HuMCs, showed less degranulation than diluent controls, as measured by surface CD63 expression. MCs lacking PDE3 or treated with the PDE3i enoximone exhibited a lower calcium flux upon stimulation with ionomycine. In conclusion: PDE3 plays a critical role in basophil and mast cell degranulation and therefore its inhibition may be a treatment option in allergic disease.